Determining Minimum Compensation for Lost Farmland: a theory-based impact evaluation of a land grab in Sierra Leone - Marc Hansen; Mohamed Conteh; Martina Shakya; Wilhelm Löwenstein (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2016)
The land grabbing issue has produced a plethora of debates ranging from ethical conduct of land grabbing agents, specifically concerning displacement, to evidence for and against positive externalities such as technological spill-overs and construction of infrastructure. An underexplored topic is the valuation of agricultural land and the compensatory payments made to land users, distinct from land owners, for the loss of their source of food security. This paper establishes a theoretical framework for the valuation of agricultural land from the perspective of land users, based on a household production function. For the analysis data were collected in a survey of 203 households in the land grab affected area in the Northern Province of Sierra Leone during 2013. It shows that, for the case of a specific land grab in Sierra Leone, the compensatory payments received by land users are far below the value of the land lost and as such the lease income is unable to allow these households to maintain their previously, already tenuous, levels of food security. A clear distinction is made between land owners and even more vulnerable non-landowning land users who depend on the agricultural land for their food security and livelihoods. The household level analysis showed that in addition to the level of compensation received by the average household being insufficient to maintain a priori welfare levels the distribution of compensation significantly favoured the wealthier households. Since the value of the land and the rent distribution were set in local positive law the project could correctly call itself fully compliant but the land grab still resulted in significant welfare losses. The methodology implemented by this ex-post study can identically be applied to an ex-ante scenario allowing land grabbing agents to define a minimum compensatory payment to land users not based on asymmetrical bargaining power but on actual land value to this vulnerable section of the local population.
Keywords: D13; D61; H43; Q12; Q15; R52; 330; Land Grabbing; Large Scale Land Leases; Productivity Method; Theory-Based Impact Evaluation; Smallholder Farmers; Customary Land Rights; Welfare Changes; Sierra Leone; Bodenrecht; Enteignung; Agrareinkommen; Agrarproduktion; Soziale Folgen; Sierra Leone